MOLECULAR CHARACTERIZATION OF TWO ACETYLCHOLINESTERASE GENES FROM THE RICE LEAFFOLDER, Cnaphalocrocis medinalis (LEPIDOPTERA: PYRALIDAE). Issue 3 (22nd July 2016) - Wang, Dong‐Ming; Zhang, Bang‐Xian; Liu, Xiao‐Ming; Rao, Xiang‐Jun; Li, Shi‐Guang; Li, Mao‐Ye; Liu, Su
Abstract : In this study, two full‐length cDNA sequences ( Cmace1 and Cmace2 ) encoding putative acetylcholinesterases (AChEs) were cloned and characterized from the rice leaffolder, Cnaphalocrocis medinalis, an important lepidopteran rice pest in Asia. Cmace1 encodes a CmAChE1 consisting of 689 amino acid residues, while Cmace2 encodes a 639 amino acids CmAChE2. The two CmAChEs both have N‐terminal signal peptides and conserved motifs including the catalytic triad, choline‐binding sites, oxianion hole, acyl pocket, peripheral anionic subsite, and the characteristic FGESAG motif and conserved 14 aromatic amino acids. Phylogenetic analysis showed that Cmace1 and Cmace2 are clustered into distinct clusters that are completely diverged from each other. Reverse‐transcription quantitative PCR analysis revealed that Cmace1 and Cmace2 were predominately expressed in the larval brain and at the fifth‐instar larvae stage, and the transcription levels of Cmace1 were significantly higher than those of Cmace2 in all the tested samples. Recombinant CmAChE1 and CmAChE2 were heterologously expressed in baculovirus system. Using acetylthiocholine iodide (ATChI) as substrate, the Michaelis constant ( K m ) values of rCmAChE1 and rCmAChE2 were 39.81 ± 6.49 and 68.29 ± 6.72 μmol/l, respectively; and the maximum velocity ( V max ) values of the two rCmAChEs were 0.60 ± 0.02 and 0.31 ± 0.06 μmol/min/mg protein, respectively. Inhibition assay indicated that rCmAChE1 was more sensitive to the organophosphate insecticides chlorpyrifos and triazophos than rCmAChE2. This study is the first report of molecular cloning and biochemical characterization of two acetylcholinesterase genes/enzymes in C. medinalis .